Metal Complexes of 6-Acetyl-4-aryl-2-ethoxycarbonyl-1,2,3,4-tetrahydro-1,2,4,5-tetrazine Oximes - M. Awadallah, Adel; S. Ferwanah, Abdel-Rahman; M. Awad, Boshra; M. El-Halabi, Nabil (Asian Journal of Chemistry, 2016)
Nitrilimines (5a-c) react with 1-ethoxycarbonyl-1-methylhydrazine (6) to give the corresponding 3-acetyl-1,2,4,5-tetrazines (8a-c). Oximes of these tetrazines (9a-c) and their Pd(II) (10a) and Ni(II) (11b) complexes were prepared and characterized using IR, MS, NMR and electronic spectra.